Fault Factor Analysis in Complicated Electrical Engineering - Zhang, Yagang; Zhao, Zheng; Sun, Yi; Wang, Zengping (Elektronika ir Elektrotechnika, 2013)
Wide area adaptive backup protection is one of the research hotspots in complicated electric power system field. The researches in this paper are mainly serving wide area protection system. We will study a novel fault factor analysis in complicated electric power system, and this scheme can reduce the influence of relay protection’s wrong action device on fault detection. It has been proved by a large number of simulation experiments, even if there is the influence of random disturbance, the system failure in electric power system can be rapidly and effectively analysed by utilizing a fault factor analysis scheme. DOI: http://dx.doi.org/10.5755/j01.eee.19.10.2909